2019
DOI: 10.1007/s10461-019-02416-9
|View full text |Cite
|
Sign up to set email alerts
|

Network Properties Among Gay, Bisexual and Other Men Who Have Sex with Men Vary by Race

Abstract: The HIV burden among gay, bisexual, and other men who have sex with men (GBM) may be related to variations in network characteristics of the individual's social and sexual network. This study investigates variations in network properties among 188 Black and 295 White GBM recruited in New Orleans during the National HIV Behavioral Surveillance in 2014. Participants described up to five people who provided social support and five sex partners in the past three months. Network properties and network dissimilarity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…21,22 Sexual network characteristics, not individual behaviors, account for the higher prevalence of HIV among Black MSM. 23,24 Studies of sexual partnership mixing in both heterosexual and MSM networks have demonstrated that people in racial or ethnic minority groups often have sex partners of the same race/ ethnicity, contributing to worsening disparities in STIs. 25,26 As sexual networks and social factors such as poverty and discrimination drive disparities in STI rates in the United States, 27 effective prevention of syphilis will require multidisciplinary collaborations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Sexual network characteristics, not individual behaviors, account for the higher prevalence of HIV among Black MSM. 23,24 Studies of sexual partnership mixing in both heterosexual and MSM networks have demonstrated that people in racial or ethnic minority groups often have sex partners of the same race/ ethnicity, contributing to worsening disparities in STIs. 25,26 As sexual networks and social factors such as poverty and discrimination drive disparities in STI rates in the United States, 27 effective prevention of syphilis will require multidisciplinary collaborations.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies and frameworks have demonstrated the interaction of individual behaviors, social and sexual networks, sociocultural contexts, and community prevalence in the prevention of STIs 21,22 . Sexual network characteristics, not individual behaviors, account for the higher prevalence of HIV among Black MSM 23,24 . Studies of sexual partnership mixing in both heterosexual and MSM networks have demonstrated that people in racial or ethnic minority groups often have sex partners of the same race/ethnicity, contributing to worsening disparities in STIs 25,26 .…”
Section: Discussionmentioning
confidence: 99%